2017
DOI: 10.20944/preprints201705.0012.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<em>Leptadenia reticulata</em> (Retz.) Wight (Jivanti): Botanical, Agronomical, Phytochemical, Pharmacological, and Biotechnological Aspects

Abstract: Leptadenia reticulata (Ritz.) Wight (Asclepiadaceae), a traditional medicinal plant species, is widely used in traditional medicine to treat various ailments such as tuberculosis, hematopoiesis, emaciation, cough, dyspnea, fever, burning sensation, night blindness, cancer, and dysentery. In Ayurveda, it is known for its revitalizing, rejuvenating, and lactogenic properties. This plant is one of the major ingredients in many commercial herbal formulations, including Speman, Envirocare, Calshakti, Antisept, and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…The fact that the ethanolic extract of leaves of Mitragyna parvifolia exhibited inhibitory activities against some of the microorganisms implicated in the pathogenesis of bacterial and skin diseases (Escherechia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Candida albicans, Microsporum gypseum and Aspergillus niger) provides some scientific basis for the utilization of this plant in traditional Indian systems of medicine and as alternative to commercially available high cost medicines for the treatment of bacterial and skin diseases. 16 Based on the test data, further chemical and pharmacological investigations may be recommended for Mitragyna parvifolia.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the ethanolic extract of leaves of Mitragyna parvifolia exhibited inhibitory activities against some of the microorganisms implicated in the pathogenesis of bacterial and skin diseases (Escherechia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Candida albicans, Microsporum gypseum and Aspergillus niger) provides some scientific basis for the utilization of this plant in traditional Indian systems of medicine and as alternative to commercially available high cost medicines for the treatment of bacterial and skin diseases. 16 Based on the test data, further chemical and pharmacological investigations may be recommended for Mitragyna parvifolia.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Quercetin compounds have an active role in Leptadenia reticulata (Apocynaceae) and are used to treat different ailments such as cancer, CVS, allergies, diabetes, immunomodulatory, and anti-infective properties. [8][9][10] L. reticulata, traditionally known as "Jivanti", is a popular plant that is used as a drug in the Indian ayurvedic system of medicine and folklore practice. It is well documented in Ayurveda for its revitalizing, renewing, and lactogenic properties.…”
Section: Original Articlementioning
confidence: 99%
“…Despite the fact that earlier research has reported that quercetin was assessed and measured using analytical techniques such as HPLC and HPTLC. [8,14] However, validation parameters were not done for quercetin in L. reticulata using the HPTLC method. [15] Secondary metabolites are not stable in geographically collected herbal plants, according to previous studies.…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations